2022
DOI: 10.1002/jcsm.12904
|View full text |Cite
|
Sign up to set email alerts
|

Obesity attenuates inflammation, protein catabolism, dyslipidaemia, and muscle weakness during sepsis, independent of leptin

Abstract: Background Muscle weakness is a frequently occurring complication of sepsis, associated with increased morbidity and mortality. Interestingly, obesity attenuates sepsis‐induced muscle wasting and weakness. As the adipokine leptin is strongly elevated in obesity and has been shown to affect muscle homeostasis in non‐septic conditions, we aimed to investigate whether leptin mediates the protective effect of obesity on sepsis‐induced muscle weakness. Methods In a mouse model of sepsis, we investigated the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“… 9 Although the mechanism underlying the inverse correlation between VFI and SII remains unclear, suppressive pathways that counteract the chronic inflammatory status during obesity-associated inflammation could be a possible explanation. 8 Vankrunkelsven et al 45 also reported that obesity attenuates inflammation during sepsis, with a 50% decrease in plasma tumor necrosis factor-α increase in leptin-deficient and diet-induced mice with obesity compared with that in lean mice. However, the possibility of reverse causation still exists, given that our results are based on observational studies and cannot determine the true causal relationships between VFI and SII.…”
Section: Discussionmentioning
confidence: 98%
“… 9 Although the mechanism underlying the inverse correlation between VFI and SII remains unclear, suppressive pathways that counteract the chronic inflammatory status during obesity-associated inflammation could be a possible explanation. 8 Vankrunkelsven et al 45 also reported that obesity attenuates inflammation during sepsis, with a 50% decrease in plasma tumor necrosis factor-α increase in leptin-deficient and diet-induced mice with obesity compared with that in lean mice. However, the possibility of reverse causation still exists, given that our results are based on observational studies and cannot determine the true causal relationships between VFI and SII.…”
Section: Discussionmentioning
confidence: 98%
“…An early elevated UCR helped predict the development of ICUAW in patients with sepsis. The pronounced muscle wasting that contributed to the weakness of myogenic origin in sepsis patients was explained by the catabolic state of critical illness, with decreased anabolic effector hormones and increased catabolic hormones [21,22] , as well as the mechanical unloading brought on by immobilization or denervation. This metabolic disorder led to an increase in protein catabolism and a decrease in anabolism [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested similar longitudinal profiles of urea and creatinine suggesting this is an effect observed nonpolytrauma critically ill patients [48]. Subsequent recent studies have echoed the utility of urea:creatinine ratio as a marker of muscle wasting [49]. The UCR have been used in a secondary analysis of multicentre trial data of ICU patients to assess the impact of novel nutritional strategies such as intermittent versus continuous feeding [50].…”
Section: The Urea To Creatinine Ratio As a Biological Signature For N...mentioning
confidence: 99%